2014
DOI: 10.1111/dewb.12069
|View full text |Cite
|
Sign up to set email alerts
|

To What did They Consent? Understanding Consent Among Low Literacy Participants in a Microbicide Feasibility Study in Mazabuka, Zambia

Abstract: We conducted a study to review the consenting process in a vaginal microbicide feasibility study conducted in Mazabuka, Zambia. Participants were drawn from those participating in the microbicide study. A questionnaire and focus group discussion were used to collect information on participants' understanding of study aims, risks and benefits. Altogether, 200 participants took part in this study. The results of the study showed that while all participants signed or endorsed their thumbprints to the consent form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Our findings indicate that participants had a good understanding of the RCT and concepts such as randomization and placebo, and their consent appeared informed. These findings are in context of previous reports expressing concern about informed consent in RCTs, particularly those using a placebo, and in low-literacy populations (Manafa, Lindegger, & Ijsselmuiden, 2007; Munalula-Nkandu, Ndebele, Siziya, & Munthali, 2014).…”
Section: Discussionsupporting
confidence: 87%
“…Our findings indicate that participants had a good understanding of the RCT and concepts such as randomization and placebo, and their consent appeared informed. These findings are in context of previous reports expressing concern about informed consent in RCTs, particularly those using a placebo, and in low-literacy populations (Manafa, Lindegger, & Ijsselmuiden, 2007; Munalula-Nkandu, Ndebele, Siziya, & Munthali, 2014).…”
Section: Discussionsupporting
confidence: 87%
“…Both junior and senior researchers worried about "cut and paste" approaches to consent forms that negated the importance of ensuring the language and information in forms were adapted to specific populations, participant education level(s), particular concerns, and prior exposure to information, studies, or methods. These practical complexities and concerns are well founded, and echo those raised by researchers and ethicists interested in the quality and challenges of informed consent in African clinical research (13,(31)(32)(33)(34). In a systematic review that looked at clinical research participant understanding for consent, across 21 African studies, over 50% of participants were found to have consented without understanding key concepts relevant to the study in which they volunteered (35).…”
Section: Challenge Area 1: Consent Form Preparation For National Revi...mentioning
confidence: 95%
“…generally poor comprehension of the benefits and harms outlined in the consent process 44 and the empirical difficulties of securing understanding and recall. 16,42,45,46 This suggests that important aspects of PFSs that may not readily be grasped by potential participants should be actively explored with them, rather than simply being stated in consent documentation. 47 Asking participants to state their own understanding or expectations of the study at the outset may help.…”
Section: Practical Considerationsmentioning
confidence: 99%